Mechanistic insights from targeted molecular profiling of repolarization alternans in the intact human heart - Orini, Michele (Europace, 2019)
AIMS: Action potential duration (APD) alternans is an established precursor or arrhythmia and sudden cardiac death. Important differences in fundamental electrophysiological properties relevant to arrhythmia exist between experimental models and the diseased in vivo human heart. To investigate mechanisms of APD alternans using a novel approach combining intact heart and cellular cardiac electrophysiology in human in vivo. METHODS AND RESULTS: We developed a novel approach combining intact heart electrophysiological mapping during cardiac surgery with rapid on-site data analysis to guide myocardial biopsies for laboratory analysis, thereby linking repolarization dynamics observed at the organ level with underlying ion channel expression. Alternans-susceptible and alternans-resistant regions were identified by an incremental pacing protocol. Biopsies from these sites (n = 13) demonstrated greater RNA expression in Calsequestrin (CSQN) and Ryanodine (RyR) and ion channels underlying I(K1) and I(to) at alternans-susceptible sites. Electrical restitution properties (n = 7) showed no difference between alternans-susceptible and resistant sites, whereas spatial gradients of repolarization were greater in alternans-susceptible than in alternans-resistant sites (P = 0.001). The degree of histological fibrosis between alternans-susceptible and resistant sites was equivalent. Mathematical modelling of these changes indicated that both CSQN and RyR up-regulation are key determinants of APD alternans. CONCLUSION: Combined intact heart and cellular electrophysiology show that regions of myocardium in the in vivo human heart exhibiting APD alternans are associated with greater expression of CSQN and RyR and show no difference in restitution properties compared to non-alternans regions. In silico modelling identifies up-regulation and interaction of CSQN with RyR as a major mechanism underlying APD alternans.